A Statistical Analysis of the Relation Between Cost and Price - Simpson, Kemper (Quarterly Journal of Economics, 1921)
Marginal cost and price, 265. — Bulk-line cost, 267. — Dispersions of costs in different interests, 268. — Relations of price, cost, and gross profit on investment, 270. — Difficulties in using the Commission's costs, 271. — Book paper, 273. — Newsprint paper, 278. — Canned salmon, 281. — Sugar beets, 283. — Copper, 285. — Conclusions, 286.